2013
DOI: 10.1128/jvi.02540-13
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Transactivator Rta Induces Cell Cycle Arrest in G 0 /G 1 Phase by Stabilizing and Promoting Nuclear Localization of p27 kip

Abstract: The Kaposi's sarcoma-associated herpesvirus (KSHV) immediate-early gene, replication, and transcription activator (K-Rta) is a key viral protein that serves as the master regulator for viral lytic replication. In this study, we investigated the role of K-Rta in cell cycle regulation and found that the expression of K-Rta in doxycycline (Dox)-inducible BJAB cells induced cell cycle arrest in G 0 /G 1 phase. Western blot analysis of key cell cycle regulators reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…The S gene, also known as HBsAg, is divided into Pre-S1, Pre-S2, and S domains and encodes three envelope proteins often referred to as large (L), middle (M), and small (S). The three remaining ORFs encode a DNA polymerase (Pol), a capsid protein (core) and the 154 amino acid X protein (HBx) [ 207 ].…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…The S gene, also known as HBsAg, is divided into Pre-S1, Pre-S2, and S domains and encodes three envelope proteins often referred to as large (L), middle (M), and small (S). The three remaining ORFs encode a DNA polymerase (Pol), a capsid protein (core) and the 154 amino acid X protein (HBx) [ 207 ].…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…It was notable that a G1 block was not observed during the first 24 h following lytic replication considering that this has been reported in several studies of herpesviruses including KSHV [ 21 , 36 , 37 , 38 , 39 ]. KSHV lytic proteins RTA and K8α have both been shown to induce a G1 block when expressed in isolation [ 37 , 38 , 39 ]. However, KSHV also encodes a D-cyclin homolog, known as v-cyclin, that has been reported to induce cell cycle progression via inactivation of p27 KIP1 [ 40 ].…”
Section: Discussionmentioning
confidence: 69%
“…Using a Cdt1-eGFP fusion protein to track cell-cycle progression in live cells containing lytic virus, the authors observed that EBV RCs develop in early S phase and sequester the PCNA DNA clamp while excluding cellular DNA and histones. Previous studies demonstrating that individual expression of the KSHV lytic proteins RTA and K8α results in G1 arrest have provided additional evidence that prevention of S-phase entry is an advantageous herpesvirus adaptation [4,5]. However, it is also known that V-cyclin, a KSHV d-type cyclin homologue expressed in both the latent and lytic phases, inactivates p27 promoting cell-cycle progression through G1 into S phase [24].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed rationale was that, by restricting S-phase entry, the virus avoids competition with cellular DNA for replication resources. In support of these findings, both the KSHV immediate-early proteins RTA and K8α have been shown to negatively regulate the G1/S transition when expressed alone [4,5]. In contrast, another study presented evidence that S phase provides a more conducive environment for KSHV replication due to upregulation of genes that promote DNA replication, cell survival and lipid metabolism [6].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation